Evaluating financial viability of boilers in palm oil mills under processing capacity variability: a case study approach - Nur Chairat, Arief Suardi; Abdullah, Lokman; Caswito, Ade; Pangestu, Galuh Adi; Kefli, Muhammad Hamdi; Md Fauadi, Muhammad Hafidz Fadzli; Mohd Aras, Mohd Shahrieel (Business, Management and Economics Engineering, 2026)
Purpose – This study evaluates the financial feasibility of boiler investments in palm oil mills, examining the variability in processing capacities resulting from seasonal yields and operational constraints. Research methodology – A case study was conducted at a palm oil mill in Indonesia, assessing five investment scenarios through sensitivity analysis to compare repair and new boiler strategies at capacities of 48, 51, and 58 tons of FFB per hour. Financial metrics including Net Present Value (NPV), Internal Rate of Return (IRR), and payback period were employed. Findings – Results exhibit that repairing the boiler, specifically at a capacity of 58 tons/hour, provides the greatest financial returns, with a Net Present Value (NPV) of USD 9.5 million and an Internal Rate of Return (IRR) of 21%, surpassing investments in new boilers. Scenario 5 demonstrated the highest financial resilience in response to variations in costs and revenues. Research limitations – This research is based on financial assumptions and a singular case study context. Wider generalizations necessitate analysis across various operational contexts. Practical implications – The findings provide decision-making tools for palm oil mills to optimize capital expenditure in relation to capacity variability and cost efficiency. Originality/Value – This research incorporates operational variability into financial modeling, offering a novel perspective on boiler investment strategies within the palm oil sector.